Out of this earth : East India Adivasis and the aluminum cartel - Padel, Felix (New Delhi, 2010)
Out of this Earth is a penetrating anthropological study that uncovers the hidden history behind mining projects in tribal areas of south Odisha. Capping its largest mountains are some of the world$1 (Bs best bauxite deposits, promising prosperity to one of India$1 (Bs poorest states. Entrenched capitalist notions of development collide with the locals' perception of metal factories as a new colonial invasion. Tribal people who have lived around them since history began, do not see these mountains as a resource to be exploited, but a source of life itself. Meticulously researched, this seminal book brings to light the displacement and cultural genocide of adivasis, alongside hideous scams and pollution. It lays bare the complicated and bloody history of the aluminium industry, at the heart of the military-industrial complex.s
Keywords: Scheduled tribes-East india